2010
DOI: 10.1590/s0103-21002010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade funcional em indivíduos com lesão de medula espinhal

Abstract: Objectives:To investigate the characteristics of individuals with spinal cord injury being treated in public hospitals, in Ribeirao Preto, Sao Paulo, and to assess the functional independence according to the degree of injury, the time after injury and the rehabilitation. Methods: Is a cross-sectional observational study conducted from January 2003 to July 2006, comprising 22 patients being treated on these hospitals, with assessment of functional capacity through the Functional Independence Measure (FIM) scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
12

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 14 publications
2
19
0
12
Order By: Relevance
“…With regard to the sociodemographic characteris cs of individuals with TSCI, these were highlighted by other studies repor ng that the popula on most aff ected by TSCI is that of young adults, aged 18 to 35 years, and overwhelmingly of the male gender (1,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…With regard to the sociodemographic characteris cs of individuals with TSCI, these were highlighted by other studies repor ng that the popula on most aff ected by TSCI is that of young adults, aged 18 to 35 years, and overwhelmingly of the male gender (1,(11)(12)(13) .…”
Section: Discussionmentioning
confidence: 98%
“…Depending on the neurological level of injury, these individuals need assistance for the total or par al performance of ADLs, such as dressing, pu ng on shoes, bathing, and ea ng. The higher the neurological level of spinal cord injury, as in the case of quadriplegic pa ents, the greater the me spent in care (1,11,16) , because individuals with TSCI, especially quadriplegics, are dependent on long-term care and the lack of, or failure in, the planning of care can lead to caregiver burden.…”
Section: In November Of 2011 the Federal Government Established The mentioning
confidence: 99%
See 1 more Smart Citation
“…However, clinical practice shows that early inserts in rehabilitation programs has a great value in predicting functional independence [16] [26].…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the results of rehabilitation of persons with SCI showed significant increases in functional capacity regardless of the type of injury, however noted that people with tetraplegia stay longer in the rehabilitation center [16] [27] [28].…”
Section: Discussionmentioning
confidence: 99%